Translational Researches Require Effective Protocols for Knowledge and Technology Transfer and Integration - Yadollah Omidi (BioImpacts, 2011)
Integration of several disciplines (nonclinical, preclinical and clinical researches) during drug discovery and development through learn and confirm process need a dynamic process “translational medicine” (TM) to give a holistic understanding of the entire process. To achieve the highest impacts, however, effective standard protocols need to be performed.